2023
DOI: 10.1021/acssuschemeng.2c04949
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Polymorphic Heterostructures of MoS2–WS2 (1T/1T, 2H/2H) for Efficient Hydrogen Evolution Reaction

Abstract: Earth-abundant and inexpensive transition metal dichalcogenides (TMDCs) with existing polymorphisms (metallic 1T phase and semiconducting 2H phase) have been proposed as alternatives to noble metals (e.g., Pt, Ir, and Ru) to achieve an efficient hydrogen evolution reaction (HER). Although the 1T phase of TMDCs (1T-TMDCs) is essential as an HER catalyst, practical application in the HER has not been realized owing to the lack of any large-scale production of the 1T-TMDC and 1T/1T-TMDC heterostructure fabricatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…Noh et al [54] found MoS 2 C-edge on a WSe 2 support has ∆G H * = −0.008 eV at 1/4 ML. Seok et al [94] found 1T-MoS 2 /1T-WS 2 vertical heterostructures to perform well in HER. However, this particular heterostructure was not studied in [54].…”
Section: On Synergy With Experimentsmentioning
confidence: 99%
“…Noh et al [54] found MoS 2 C-edge on a WSe 2 support has ∆G H * = −0.008 eV at 1/4 ML. Seok et al [94] found 1T-MoS 2 /1T-WS 2 vertical heterostructures to perform well in HER. However, this particular heterostructure was not studied in [54].…”
Section: On Synergy With Experimentsmentioning
confidence: 99%
“…The presence of plasma can reduce impurities such as adventitious carbon, increase substrate affinity for interaction with gaseous precursors by surface activation, and result in a better uniformity and adhesion to substrate . In an atmospheric-pressure PECVD technique (Figure a as well as Figure a,b), MoS 2 and WS 2 multilayers as well as their heterostructures can directly be grown onto various substrates such as polyethylene terephthalate (PET) and Si at temperatures below 200 °C. At an operational temperature of 150 °C, it is possible to directly synthesize 1T-MoS 2 and 1T-WS 2 thin films as well as their heterostructures that cannot be attained via conventional CVD methods. …”
Section: Plasma-assisted Synthesis Of Tmdsmentioning
confidence: 99%
“…In the past few years, advanced research has been conducted for the exploitation of Earth-abundant and efficient electrocatalysts toward the HER; for instance, transition metal sulfides and carbides, e.g., MoS 2 , WS 2 and Mo 2 C have shown excellent performance due to their similar electronic structures to that of Pt. [5][6][7][8][9][10][11][12] Polyoxometalates (POMs) are a class of metal oxide cluster compounds constituted of pre-transition metals (V, Mo, W, Nb, etc. ), which have been widely used in the fields of catalysis, energy and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…, MoS 2 , WS 2 and Mo 2 C have shown excellent performance due to their similar electronic structures to that of Pt. 5–12…”
Section: Introductionmentioning
confidence: 99%